Activation of mental imagery neural network revealed during listening to Fatihah Chapter; a neuroimaging study (Bangladesh Journal of Medical Science, 2022)
Background: Listening to Quranic recitation has been claimed to enhance educational performance and cognitive functionality. Unfortunately, scientific evidence for this remains scarce.Aim: Hence, we aimed to investigate the neural mechanism underlined the psychoacoustic and cognitive enhancement effects from listening to Quranic recitation. Occipital lobe beta rhythms (14-30 Hz) were excerpted from electroencephalography (EEG) data during psychoacoustic stimulation from sham (Rest), Arabic news and the Fatihah Chapter recitation. The stimulation comes in random sequence in the same length of duration of 5,8,6,6,10, 8 and 20 seconds for verses 1 to 7, respectively. The brain’s oscillatory waveforms were pre-processed using EGI System and then were analysed by Fast Fourier Transform (FFT) to derive the power spectrum in the Beta frequency band (14-30 Hz). Data were analysed by repeated-measures ANOVA and Discriminant Analysis from XLSTAT statistical package.Result: A profound and significant reduction of the power spectrum was found in the left occipital lobe while listening to theFatihah Chapter. In contrast, no significant changes were observed in the occipital lobe during listening to Arabic news. It may be postulated that listening to the Fatihah Chapter activates an oscillatory neural network associated with visual mental imagery.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 710-716